2014
DOI: 10.1371/journal.pone.0105109
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Sickle Cell Disease and Other Hemoglobin Variants in 10,095 Lebanese Neonates

Abstract: Hemoglobinopathies are highly prevalent diseases and impose a public health burden. Early diagnosis and treatment can ameliorate the course of these diseases and improve survival. Despite purported high incidence of hemoglobinopathies in Lebanon, there are no nationwide screening programs. In this study, newborn screening utilizing high pressure liquid chromatography was executed in all public hospitals across Lebanon between 2010 and 2013. All newborns with an abnormal hemoglobin (Hb) were offered genetic cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“…Another factor that could have affected our results could be due to the change in the ethnic background, as reported by Khoriaty et al. 25 Also our results were lower than some of the reported prevalence of Sickle Cell Trait internationally. In a study conducted by Ojudu et al, it was reported that in 44 states of the United States for which data were available, of all infants screened for the Sickle Cell Trait in 2010, 1.5% tested positive.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Another factor that could have affected our results could be due to the change in the ethnic background, as reported by Khoriaty et al. 25 Also our results were lower than some of the reported prevalence of Sickle Cell Trait internationally. In a study conducted by Ojudu et al, it was reported that in 44 states of the United States for which data were available, of all infants screened for the Sickle Cell Trait in 2010, 1.5% tested positive.…”
Section: Discussioncontrasting
confidence: 62%
“…The carrier rate of Hb variant varried amongst regions, between 5.7 and 50.2%, being the highest in Northern Lebanon, whereas it is 13.2% (0.27% of the studied population) in Beirut. 25 …”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization estimates that 21.7% of people in the Middle East region carry variants for either SCD or thalassemias (Modell & Darlison, 2008;World Health Organization, 2006). In Lebanon, a recent study found that among newborns, 2.1% were found to have an abnormal hemoglobin variant, with sickle hemoglobin being the most common variant (84%) and carrier rates being highest in Northern Lebanon (Khoriaty et al, 2014). These estimates may be lower than the actual incidence because of the early discharge of newborns and lack of newborn screening at many institutions.…”
mentioning
confidence: 98%
“…The term refers to a collection of autosomal-recessive genetic disorders characterized by the hemoglobin S (HbS) variant of the b-globin gene that is resistant to malaria development and in which more than 50% the hemoglobin-b gene is replaced with HbS (El-Hazmi, Al-Hamzi, & Warsy, 2011;Saraf et al, 2014). SCD affects 1 in 500 African Americans and more than 30 million people worldwide, with predominance in populations of the sub-Sahara, India, and the Middle East (Inati et al, 2007;Khoriaty et al, 2014;McGann, 2014). There are different variants of the b-globin gene in SCD, including but not limited to sickle cell anemia, sickle-hemoglobin C disease, sickle beta-plus thalassemia, and sickle beta-zero thalassemia, with prevalence of certain variants types in particular ethnic groups (El-Hazmi et al, 2011;Saraf et al, 2014).…”
mentioning
confidence: 99%
“…Once the presence and provenance of blood has been demonstrated, it is, in theory, possible to obtain a plethora of additional information from it. Considering various blood diseases and protein variants like haemoglobinopathies, it might be possible to determine if the injured is suffering from a particular disease such as sickle cell disease [85], diabetes [86][87][88] or even myocardial infarction [89]. It can be hypothesized that this can narrow down the search by indicating that the injured will have to be taking a certain medication to treat the condition.…”
Section: Blood Evidencementioning
confidence: 99%